O exercício profissional do assistente social na perspectiva da instrumentalidade - Peretti, Edriane Cristhina Catarin (2016)
The professional practice of social work understood based on instrumentality as mediation field, enables the social worker to provide the visibility and social recognition of the profession. Based on this understanding, purpose is to achieve the dissertation, analyze professional practice from the use of instrumental by social workers of Dental State Center for Special Patients - CEOPE in the city of Cuiabá/MT. To this end, it was defined as research problem: How professional practice constitutes a mediator practice in the use of instrumental? In this sense, the limits and possibilities of the instruments in the practice were identified, considering the instrumentality articulated in three dimensions: the theoretical-methodological, ethical-political and technical-operative. Methodologically adopted the qualitative research in order to cover the desk research and field research. Moreover, it was used as data collection, semi-structured interview and questionnaire with four social workers of CEOPE. The central conceptual references passed on instrumentality and professional practice. The research has as main result the visibility and social recognition of the profession in the CEOPE intervention space, constructed and attached by professionals through the use of instruments in the practice.